Cross banking transaction system using multichain blockchain systems - Sharar, Shihab; Morshed, Ishfaq; Sadia, Kazi Sumaia (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.